2012
DOI: 10.5039/agraria.v7isa1906
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades químicas de um solo cultivado com duas forrageiras fertirrigadas com esgoto doméstico tratado

Abstract: Com o objetivo de avaliar as alterações químicas de um solo cultivado com as forrageiras Tifton 85 (Cynodon spp) e Capim Marandu (Brachiaria brizantha), fertirrigadas com esgoto doméstico tratado, foi montado um experimento em parcelas subdivididas, no esquema fatorial 2x5, com cinco repetições. Os fatores nas parcelas correspondem a duas forrageiras (Tifton 85 e Capim Marandu) e nas subparcelas cinco tratamentos, sendo um fertilizado com adubação mineral, ao qual foram aplicados 40 kg ha-1 de nitrogênio e qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
1
1
0
3
Order By: Relevance
“…Other attributes, such as organic matter and nitrogen, also showed differences in this type of experiment; however the differences are dependent on concentrations in the TSE, the application period and the respective climatic and soil conditions. Garcia et al (2012), cultivating fertirrigated forages with TSE confirmed increases in the levels of phosphorus, potassium and base saturation, a fact that in the present study only occurred with potassium.…”
Section: Chemical Attributes Of the Soilsupporting
confidence: 80%
“…Other attributes, such as organic matter and nitrogen, also showed differences in this type of experiment; however the differences are dependent on concentrations in the TSE, the application period and the respective climatic and soil conditions. Garcia et al (2012), cultivating fertirrigated forages with TSE confirmed increases in the levels of phosphorus, potassium and base saturation, a fact that in the present study only occurred with potassium.…”
Section: Chemical Attributes Of the Soilsupporting
confidence: 80%
“…Resultados semelhantes ao presente trabalho foram encontrados por Kouraa et al (2002) e Mendes et al (2016), que não verificaram diferença estatística nos teores de K + entre os tratamentos com água de abastecimento e efluente de esgoto doméstico tratado. Entretanto, Garcia et al (2012) constataram acréscimo no teor de K + , com a aplicação de doses crescentes de esgoto doméstico Tabela 4. Razão de adsorção de sódio no solo (mmol L -1 ) 0,5 , sob tratamento com ED Dose (m 3 ha -1 )…”
Section: Resultsunclassified
“…Nitrogen were found in concentrations of 17 to 35 mg L -1 , which is suitable for most crops grown in the study environment (RIBEIRO et al, 2012;ANDRADE FILHO et al, 2013). Higher concentrations were found in sewage treatment systems in the Brazilian Southeast region (Araras, SP; Alegre, ES; and Botucatu, SP), ranging from 45 to 77 mg L -1 , (GARCIA et al, 2012;PINTO et al, 2013;SOUZA et al, 2015).…”
Section: Domesticmentioning
confidence: 98%